Revisiting the Role of Acetylcholinesterase in Alzheimer’s Disease: Cross-Talk with P-tau and β-Amyloid - García-Ayllón, Maria-Salud; Small, David H; Avila, Jesus; Saez-Valero, Javier (Frontiers in Molecular Neuroscience, 2011)
A common feature in the Alzheimer’s disease (AD) brain is the presence of acetylcholinesterase (AChE) which is commonly associated with β-amyloid plaques and neurofibrillary tangles. Although our understanding of the relationship between AChE and the pathological features of AD is incomplete, increasing evidence suggests that both β-amyloid protein (Aβ) and abnormally hyperphosphorylated tau (P-tau) can influence AChE expression. We also review recent findings which suggest the possible role of AChE in the development of a vicious cycle of Aβ and P-tau dysregulation and discuss the limited and temporary effect of therapeutic intervention with AChE inhibitors